PELAKSANAAN KEGIATAN ELABORASI PEMBELAJARAN SEJARAH DI SMA NEGERI 2 BAYANG KABUPATEN PESISIR SELATAN - Meiyani, Dona; Zafri, Zafri; Nazmi, Ranti (Pendidikan Sejarah, 2014)
This research was partly motivated by the history teacher is still teaching method based on applying the old habits , the teacher is more likely to use lecture and question and answer , and the teacher used to give the record a lot of the students at SMAN 2 Bayang District South coast . On the basis of the problem of this research is focused on the implementation of learning in introductory activities , core activities and events covering the history of learning social studies in SMA 2 Bayang South Coastal District . This study aims to determine the implementation of core activities , ie the Elaboration of activities undertaken in the process of teaching social studies teacher at SMAN 2 history Bayang South Coastal District .Â Based on these problems , the type of research used in this study is descriptive evaluative study , to test the validity of the data the authors used data triangulation . Then the techniques of data analysis in this study using the interactive analysis technique proposed by Huberman Milles , which consists of data collection , data reduction , data display and conclusion drawing / verification .The results showed , that the history teacher at SMAN 2 Bayang South Coastal District . Teachers have understood the purpose of elaboration activities , but can not fully implement learning activities in accordance with the purpose of elaboration .The results of the study concluded that the implementation of the teaching and learning process in the core activities in the process of elaboration by historical subject teachers at SMAN 2 shadow has not been implemented in accordance with existing guidelines according Permendiknas 41 in 2007 .